Pengaruh Peran Influencer dan Social Media Marketing Terhadap Minat Beli Sandal Crocs : Studi Kasus pada Mahasiswa Manajemen Universitas Pembangunan Panca Budi Medan - Dian Putri Ramadhani; Annisa Sanny; Mila Arasy; Siti Maisyarah (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2025)
The purpose of this study is to see how the role of influencers and social media marketing has an impact on the interest of Universitas Pembangunan Panca Budi management students in buying Crocs sandals. This research falls into the associative quantitative category. This research involved 5,695 management students of Universitas Pembangunan Panca Budi Medan batch 2023 and 2024 who are familiar with Crocs sandals. This study used purposive sampling technique and Slovin’s formula to select 99 respondents aged 18-25 years from the Management Study Program of Universitas Pembangunan Panca Budi. Primary data and secondary data were collected through literature studies and questionnaires with a Likert scale. Validity and reliability tests were conducted on all statement items; influencer role variables (X1), social media marketing (X2), and purchase intention variables (Y) were declared valid and reliable; multiple linear regression, partial test (T), simultaneous test (F), and coefficient of determination (R2). The classic assumption test of data is used in this study. Based on Multiple Linear Regression Analysis of influencer role variables (X1) and social media marketing (X2), there is a positive correlation to purchase intention (Y). Based on the partial test results (T test), the role of influencers (X1) has a positive and significant effect on purchase intention (Y), with a t value of 3.184 and a significance of 0.002 (smaller than 0.05). Social media marketing (X2) also has a positive and significant effect on purchase intention (Y), with a t value of 3.113 and a significance of 0.002 (smaller than 0.05). Based on the results of the simultaneous test (F test), the influencer role variable (X1) and social media marketing (X2) together have a significant influence on purchase intention (Y), with a calculated f value of 5.717 and a significance of 0.005 (smaller than 0.05). 62.0% of the variation in purchase intention (Y) is caused by the influencer role variable (X1) and social media marketing (X2). Other factors not discussed in this study affect 38.0% of the variation in purchase intention (Y).